The effect of bariatric surgery on circulating levels of lipoprotein(a): a systematic review and meta-analysis. (3rd October 2022) - Jamialahmadi, T; Reiner, Z; Alidadi, M; Kroh, M; Almahmeed, W; Ruscica, M; Sirtori, C; Santos, R D; Banach, M; Sahebkar, A
Abstract: Background: Obesity, and especially severe obesity, are strongly related to higher risk of atherosclerotic cardiovascular disease (ASCVD) morbidity and mortality. Bariatric surgery is an effective weight loss therapy for people with severe obesity and weight-related co-morbid conditions. Elevated plasma level of lipoprotein(a) [Lp(a)] is causally associated with ASCVD. Purpose: The aim of the present meta-analysis was to analyze whether bariatric surgery could influence Lp(a) concentrations. Methods: A systematic literature search in PubMed, Scopus, Embase, and Web of Science was performed from inception to May 1st, 2021. A random-effects model and the generic inverse variance weighting method were used to compensate for the heterogeneity of studies in terms of study design, treatment duration, and the characteristics of the studied populations. A random-effect meta-regression model was used to explore the association with an estimated effect size. Evaluation of funnel plot, Begg's rank correlation and Egger's weighted regression tests were used to assess the presence of publication bias in the meta-analysis. Results: Meta-analysis of 13 studies including 1, 551 patients showed a significant decrease of circulating Lp(a) after bariatric surgery (SMD: −0.438, 95% CI: −0.702, −0.174, p<0.001, I 2 : 94.05%). The results of meta-regression did not indicate any significant association between the changes in Lp(a) and duration of follow up from surgery, reduction in body mass index, or baseline Lp(a) concentration. The reduction in circulating Lp(a) was robust in the leave-one-out sensitivity analysis. Conclusions: Based on the results of the Mata-analysis we showed that bariatric surgery significantly decreases circulating Lp(a) concentrations. Funding Acknowledgement: Type of funding sources: None.